Legal reform for Syria’s war-affected children: adoption, fostering, and state responsibility in transition - Lena-Maria Möller (22166914) (2025)
The prolonged conflict in Syria has left a devastating legacy for the country’s children, with over 1 million orphaned or abandoned due to violence, displacement, or economic hardship. As Syria enters a transitional phase following the fall of the Assad regime, the legal protection and integration of these children into stable family environments has become an urgent priority. This article examines the challenges and opportunities of legal reform in Syria’s plural family law system with a focus on adoption, foster care, and state responsibility. While Islamic jurisprudence prohibits full adoption (tabannī), Christian personal status laws permit it, yet they remain excluded from jurisdiction over filiation and adoption under Syrian law. Legislative Decree No. 2 of 2023, regulating care for children of unknown filiation, offers only limited solutions: it excludes orphans whose filiation is known and bars non-Muslims from fostering foundlings who are, by legal presumption, considered Muslim. Drawing on legal frameworks from a variety of contemporary Muslim jurisdictions, this article identifies approaches that reconcile religious pluralism with child-centred legal protection. It argues for a comprehensive, inclusive legal framework that incorporates functional equivalents to adoption, addresses guardianship, naming rights, inheritance, and religious identity, and accommodates both domestic and international placements. Other Information Published in: International Journal of Law, Policy and The Family License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://doi.org/10.1093/lawfam/ebaf029